Towards the standardization of human platelet lysate production and its comparison to fetal bovine serum for human hematopoietic cell culture: a scoping review - Immalaraju, Shamili; Goyal, Srishti; Jonnalagadda, Rukmini (Frontiers in Toxicology, 2025)
Human hematopoietic cell culture (HCC) refers to the ex vivo growth of normal cells of the hematological system. These cells can be used as models to understand hematopoiesis and related malignancies. HCC also holds immense potential to help develop safer vaccines and immunotherapies, as well as donor-independent blood products. In vivo, these cells grow and differentiate in highly specialized conditions but replicating these in vitro is a significant technical challenge. Although various strategies have been developed to optimize HCC expansion, implementing them can be costly. Consequently, traditional fetal bovine serum (FBS)-containing media is the first choice, despite its disadvantages. Over the past two decades, human platelet lysate (hPL) has emerged as a viable alternative. However, variations in protocols and reporting standards across laboratories have resulted in a mixed picture regarding its feasibility to replace FBS. Thus, this study aimed to review existing literature that directly compared HCC performance in hPL and FBS supplementation. PubMed, Google Scholar, and the FCS-free database were queried between 1 January to 30 July 2024. Using pre-defined inclusion and exclusion criteria, five out of 622 relevant records were included in this scoping review. Data on the hPL production method, HCC conditions and performance were extracted. We identified gaps in the consideration of key hPL production parameters and recommend addressing them to reduce the variability observed in hPL performance. Even though hPL production parameters were repeatedly overlooked, hPL outperformed FBS supplementation in terms of cell identity and functionality across the included HCC studies. Therefore, we highlight the potential of these recommendations to overcome existing technical challenges in HCC, as well as support the development of effective FBS alternatives by enhancing the reproducibility and reporting standards of future studies.